A Beginner’s Guide to Surgical Treatment Objective – An Orthodontist’s Point of View - Diana Ashok1 , Thulasi Ram E2 , Kannan M S.3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Visualising the result of any proposed treatment, not only guides us in each part of the journey towardthe final result but also to assess if the treatment objectives are met. Any adverse effects can be easilydetermined, before the start of the treatment, and necessary alterations to the treatment plan can be made.Various methods in which the result of an orthognathic surgery can be visualised are – overlay tracing,template tracing, cephalometric prediction tracing, computer prediction, feasibility mock surgery, etc. Howto carry out these predictions are discussed in detail in this article.